IDENTIFYING NEURAL MECHANISMS OF COGNITIVE DYSFUNCTION IN ‘CHEMOBRAIN’ - (:unkn) unknown (My University, 2024)
Chemotherapy can save a cancer patient’s life but can also result in lasting cognitive impairment. This chemotherapy-related cognitive impairment (CRCI) is experienced by a subset of patients receiving chemotherapy can have a wide-ranging impact on many facets of their life, but importantly is not uniform across patients and can vary in severity, duration, and which aspects of cognition are affected. When compared to cancer patients not receiving chemotherapy treatment as well as healthy controls, those receiving chemotherapy display deficits in various cognitive domains; attention, in particular. Neuroimaging studies have investigated the relationship between cognitive dysfunction and the broad structural and functional neural underpinnings selectively compromised by chemotherapy. Results of these studies commonly cite regions of the brain associated with aspects of attentional networks, however, the exact neural mechanisms resulting in cognitive impairment remains unclear. Thus, our goal was to quantify CRCI by identifying the behavioral biomarkers of attention and altered neural mechanisms in cancer patients experiencing cognitive decline. To accomplish this goal, we conducted two longitudinal studies to address the questions of who was experiencing cognitive decline, what specific cognitive aspects were impaired, and which neurobiological mechanisms were responsible for cognitive impairment. The first longitudinal study examined subjective cognitive function as well as attentional capabilities on a range of subjective, neuropsychological, and neurocognitive measures. Cancer patients self-reported significant impairments after chemotherapy, despite performing better on neuropsychological tests. Exploratory follow-up analyses revealed that the improvement observed was artificially inflated due to practice effects. To quantify who was experiencing CRCI, we evaluated differences in cognitive abilities based on changes in self-reported cognitive function. Even after controlling for the influence of practice effects, the results were inconclusive. The second study sought to identify the neural mechanisms impacted by chemotherapy through task-based fMRI. This second study utilized self-reported cognitive functioning and a neurocognitive assessment to understand how different attentional subprocesses were affected. We observed significant longitudinal changes in brain regions involved with attentional processes in peak BOLD response and in the pattern of temporal dynamic during a task. We also demonstrated observable task-based biological differences related to subjective self-reported cognitive function. This represents a viable route to quantify CRCI by identifying neural mechanisms in those who are potentially experiencing chemotherapy-related cognitive impairment. Together, these results offer support that the alerting and filtering networks are uniquely susceptible to the effects of chemotherapy.
Keywords: Neurosciences; Cognitive psychology; Attention; Chemobrain; Chemotherapy-Related Cognitive Impairment; Cognitive neuroscience; CRCI; fMRI